Strategi Perpustakaan dalam Meningkatkan Minat Kunjung di Dinas Perpustakaan dan Kearsipan Kabupaten Pacitan - Niken Ayu Kumala Sari; Faisal Syarifudin (Jurnal Gema Pustakawan, 2024)
This study discusses Library Strategy in Increasing Visiting Interest in the Library and Archives Service of Pacitan Regency. The purpose of this study was to determine the strategies implemented by the Pacitan Regency Service to increase visiting interest and the obstacles faced. The research method used was a qualitative approach with a case study. The subjects of this study were the Head of Service, librarians, and users of the Library and Archives Service of Pacitan Regency. Data collection techniques in this study used interviews, observations, and documentation. Data analysis carried out were data reduction, data presentation, and drawing conclusions. The results of the study showed that the Library and Archives Service of Pacitan Regency carried out collection development strategies, local element strengthening strategies, and library promotion strategies to increase visiting interest of users. Meanwhile, the constrains faced by the Library and Archives Service of Pacitan Regency were low reading interest, low community responsibility towards public property, inadequate facilities and infrastructure, lack of budget, and lack of human resources and expertise. The conclusion of this study is that the efforts of the Pacitan Regency Library and Archives Service to increase public interest in visiting can be done through three main strategies, namely by developing collections, strengthening local elements, and promoting